Elevated CO2 reduces copper accumulation and toxicity in the diatom Thalassiosira pseudonana - Xu, Dong; Huang, Shujie; Fan, Xiao; Zhang, Xiaowen; Wang, Yitao; Wang, Wei; Beardall, John; Brennan, Georgina; Ye, Naihao (Frontiers in Microbiology, 2023)
The projected ocean acidification (OA) associated with increasing atmospheric CO2 alters seawater chemistry and hence the bio-toxicity of metal ions. However, it is still unclear how OA might affect the long-term resilience of globally important marine microalgae to anthropogenic metal stress. To explore the effect of increasing pCO2 on copper metabolism in the diatom Thalassiosira pseudonana (CCMP1335), we employed an integrated eco-physiological, analytical chemistry, and transcriptomic approach to clarify the effect of increasing pCO2 on copper metabolism of Thalassiosira pseudonana across different temporal (short-term vs long-term) and spatial (indoor laboratory experiments vs outdoor mesocosms experiments) scales. We found that increasing pCO2 (1000 µatm and 2000 µatm) promoted growth and photosynthesis, but decreased copper accumulation and alleviated its bio-toxicity to T. pseudonana. Transcriptomics results indicated that T. pseudonana altered the copper detoxification strategy under OA by decreasing copper uptake and enhancing copper-thiol complexation and copper efflux. Biochemical analysis further showed that the activities of the antioxidant enzymes glutathione peroxidase (GPX), catalase (CAT), and phytochelatin synthetase (PCS) were enhanced to mitigate oxidative damage of copper stress under elevated CO2. Our results provide a basis for a better understanding of the bioremediation capacity of marine primary producers, which may have profound effect on the security of seafood quality and marine ecosystem sustainability under further climate change.